Peningkatan Sistem Penggalangan Dana SLB Muhammadiyah Surya Gemilang melalui Digital Storytelling dan Digital Marketing - Yesika Maya Ocktarani; Muhammad Munsarif; Devy Maharja Pristya; Nurul Farah Izzatuna; Andrian Fahrezi; Irvan Nurmantoro (Jurnal Surya Masyarakat, 2023)
Surya Gemilang Muhammadiyah Special School is one of the charitable businesses that needs special attention for the community. Currently the school, which is located in Margosari Village, Limbangan sub-district, Kendal Regency, has 147 students with various disabilities. With the vision of providing skills and education for children with disabilities, this school does not charge tuition fees. Even schools equipped with dormitories also provide shuttle facilities for students who have limited access. As a school that does not charge fees, this school relies on the assistance of individuals and private institutions/state-owned enterprises. Since the school started operating in 2013, educators voluntarily accept wages below the regional minimum wage because they see the condition of students who need their services. However, this condition gradually becomes a burden on school operations. Often the assistance is in the form of physical or raw materials such as groceries, which are then donated back to underprivileged students. Departing from this condition, we partnered with schools to solve school management problems through workshops themed Fundraising through Digital Storytelling and Digital Marketing, which were held twice, plus a one-month mentoring period. This activity was originally intended for school members, especially teachers and the IT team, but in reality, all teachers and staff participated. The result is a video uploaded through social media platforms and the school's website. What's more important is that the fundraising system is integrated with school promotion so that activities at school can be well documented as well as material for virtual promotion and publication.